The COVID-19 survivors: Impact on skeletal muscle strength - Mendes, Renata Gonçalves; Heubel, Alessandro Domingues; Leonardi, Naiara Tais; Linares, Stephanie Nogueira; do Amaral, Vanessa Teixeira [UNESP]; Ciolac, Emmanuel Gomes [UNESP] (Elsevier, 2024)
The coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 has negatively impacted the quality of life of millions of people around the world. Although the respiratory system and its manifestations were the initial focus of disease descriptions, current knowledge has increasingly proven the devasting multiorgan disease involvement. Skeletal muscle can be affected, leading to weakness, fatigue, lower mobility, low physical performance, and poor quality of life in patients, persisting as a debilitating condition named long-COVID-19. The cause of COVID-19-related skeletal muscle impairment is likely multifactorial, including direct viral and immune-mediated damage, immobilization, sedation, intubation, and weakness acquired in the intensive care unit added to the previous comorbidities of patients. Patients critically ill and older adults are at greater risk for the detrimental effects of COVID-19 on muscle health; however, in mild to moderate cases; musculoskeletal system damage was also clearly pointed out. As the muscle is essential for daily activities, intervening early through a multiprofessional approach and reducing the damage caused by the disease is imperative. Handgrip strength and respiratory pressures are methods to evaluate muscle status. Exercise rehabilitation strategy, including respiratory muscle training, resistance, and aerobic training, and multicomponent exercise intervention have demonstrated a superior effect over control for improving peripheral and respiratory muscle strength and/or function outcomes. The purpose of this chapter is to describe an overview of the impact of the coronavirus on skeletal muscles in adults as well as its consequences, assessments methods, and evidenced-based rehabilitation.
Keywords: COVID-19; Functionality; Muscle; Musculoskeletal system; SARS-CoV-2; Strength